Expression of phosphatase and tensin homolog deleted on chromosome ten in liver of athymic mice with hepatocellular carcinoma and the effect of Fuzheng Jiedu Decoction - Yin, Li-Rong (The WJG Press and Baishideng, 2008)
AIM: To explore the expression of phosphatase and tensin homolog deleted on chromosome ten (PTEN) in liver of athymic mice with hepatocellular carcinoma (HCC) and the effect of Fuzheng Jiedu Decoction (FJD). METHODS: Forty eight male BALB/c athymic mice models were built by Bel-7402 with an indirect method. After 24 h of postoperation, the 48 athymic mice were distributed randomly into 4 groups: A, B, C, D, each group had 12 athymic mice. Group A were treated by intragastric administration with FT207 (Tegafur) for 4 wk. Group B, C and D were treated by intragastric administration with FJD (complex prescription of Chinese crude drug) that had been delegated into 3 kinds of density as the low, middle, and high for 4 wk. At last, athymic mice were put to death, live time, volume of tumors, exponent of tumors and the tumor metastasis in livers were observed; and PTEN was detected in hepatic tissue, latero-cancer tissue and cancer tissue by immunohistochemistry. RESULTS: Four weeks later, the total survival rate in treatment group (A + B + C) was 50% and higher than the control group (0%) treated by FT207, (P < 0.01). The survival rate in group A, B, C was higher than in group D, and except group A with D, there was significant differentces (Fisher’s Exact Test P = 0.05 or 0.01). And no differences were observed between the treatment groups and the control group in volume of tumors and exponent of tumors (P > 0.05). Tumor metastasis in livers of the treatment group was less than the controls (Fisher’s Exact Test, P = 0.021). The result of immunohistochemistry showed that the intensity of PTEN in latero-cancer tissue was the highest, and then the hepatic tissue, the lowest was cancer tissue (Kruskal-Wallis test, χ(2) = 60.67, P = 0.000). It also showed that the intensity of PTEN in treatment groups (A, B, C) was higher than the control group (D) (F = 5.90, P = 0.002 in hepatic tissue and F = 15.99, P = 0.000 in latero-cancer tissue and χ(2) = 26.08, P = 0.000 in cancer tissue), and group B is the highest in the treatment groups (P < 0.05, r = 0.01. respectively). However, there was no significant statistic difference between group A and group C (P > 0.05). CONCLUSION: FJD can prolong the survival time and decrease tumor metastasis in livers of these experimental mice. Mechanisms of FJD healing HCC may partially be explained by enhancing the expression of PTEN in liver.